Nitrogenous ionic groups and compounds present in drinking water on the territory of North-Bačka district - Marina Ivanović; Dušanka Paunović; Zorica Mamužić; Snežana Zlatanović (Zaštita Materijala)
In the territory of North-Bačka administrative district examination of drinking water regarding nitrogenous ionic groups and compounds during the period from 2013 to 2015 show was a slight deviation of comparing to the allowed ones. Statistical significance for the presence of ammonia in water samples was proven in samples taken from water supply of Subotica city. The lowest percentage of faulty samples was found in a year 2014 and the largest in a year 2015. Rural water supply of the Subotica city is characterized by minor differences observed in a time, with no statistical significance. However, comparing with the city water supply, the situation is much worse (in more than 40% of samples). Such a high percentage of faulty samples can be explained with existence of a huge number of non-organized water supplies in villages, as well as because of the using water from an insufficiently controlled private wells. Regarding the faulty samples, the water supply of the Bačka Topola municipality has the level of ammonia above the permitted, with deviations and statistically significant difference. Unlike the water supply of the Bačka Topola municipality, which has the lowest number of faulty samples recorded in 2013, in the rural water supply the number of faulty samples was the biggest in 2013 and the lowest in 2014. The territory of Mali Iđos municipality is characterized with a very small number of a faulty samples of drinking water regarding the presence of ammonia. For all three analyzed years, there were no major variations regarding faulty samples and no statistically significant differences. Observed by municipalities, there is a statistically significant difference in the number of faulty samples for all three years. Climate situation and the amount of rainfall during the 2014 was unusual in the Subotica city, as also at the larger territory of the Republic of Serbia. Long-term average in rainfall was exceeded, resulting with the lowest concentration of ammonia in the city water supply. Also, the lowest percentage of exceeding the limit value of ammonia in drinking water was recorded in 2014, in the rural water supply of the Bačka Topola municipality.